A New Score of Positivity in Thallium Studies of Ischemic Patients - Rafla, Samir; Gaber, Ahmed; Magdy, Gehan; Abdelaaty, Ahmed (Cardiology and Cardiovascular Medicine, 2020)
The aim of this work was to detect means to increase accuracy of prediction of Thallium perfusion results. Also, we aimed to investigate the incidence and severity of chest pain during radionuclide myocardial perfusion imaging and its relation to the stress modality. The study was conducted on two groups of patients that presented for radionuclide myocardial perfusion imaging. The first group included fifty patients subjected to exercise stress testing. The second group included fifty patients subjected to dipyridamole pharmacologic stress testing. The 2 groups were compared regarding chest pain, dyspnea, electrocardiographic changes, left ventricular dilatation, and increased lung thallium uptake. Exercise was associated with a statistically significant higher incidence and severity of chest pain compared to dipyridamole (p<0.001). The incidence and severity of chest pain were related to the number of vessel territories affected in the dipyridamole group (p=0.037), but not in the exercise group. Exercise was associated with a statistically significant higher incidence of electrocardiographic (ECG) changes compared to dipyridamole (p<0.001). There was no statistically significant difference in the incidence of left ventricular dilatation between the 2 groups. The incidence of left ventricular dilatation was related to the number of vessel territories affected in the exercise group (p=0.011) as well as the dipyridamole group (p=0.007). There was no statistically significant difference in the incidence of increased lung thallium-201 uptake between the 2 groups. The incidence of increased lung thallium-201 uptake was related to the number of vessel territories affected in the exercise group (p=0.017) but not in the dipyridamole group. We summed four parameters 1- chest pain (one or two or three points), 2- ECG changes > 1mm (two points), 3- LV dilation (two points), and 4- Lung thallium uptake (two points), so maximum can be 9